Is this coccyx fractured, or is it a normal variant? A cohort study - Toy, Serdar; Zeynel, Alperen; Zencirli, Kemal (Journal of Surgery and Medicine, 2021)
Background/Aim: The coccyx has several variants which could sometimes be confused with fractures. Our study aimed to alert physicians about the types of coccyges that can be easily confused with coccyx fractures in daily practice. Methods: Mid-sagittal and mid-coronal computerized images of 75 patients were analyzed to determine the types of coccygeal fracture, the coccyx types, number of segments, joint fusion, coccygeal bony spicules, subluxation, sacrococcygeal angle (SCA), intercoccygeal angle (ICA), and lateral deviation of the coccyx. Results: The mean age of the patients was 43.5 (13.6) years. There were 33 (44%) males and 42 (56%) females. While 57 (76%) patients were thought to have a coccygeal fracture, only 18 patients (24%) actually had them. There was a significant difference between the coccyx types mistaken for fractures and actual coccygeal fractures (P<0.001). Conclusion: It is essential to know the coccyx types and distinguish normal variants from fractures. If the difference between coccyx fractures and coccyx types is known and the patients are informed accordingly, both the loss of workforce decreases, and the necessary treatment can be started early.